EMPOWERMENT OF FISH CULTIVATION GROUPS (POKDAKAN) IN THE MINAPOLITAN AREA OF KALANGANYAR VILLAGE, SEDATI DISTRICT, SIDOARJO REGENCY - Mutia Ristina Nur Aini; Susi Hardjati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
Kalanganyar Village, Sedati District, Sidoarjo Regency is a village with the nickname